Neutron protein crystallography hydrogen, protons, and hydration in bio-macromolecules - Niimura, Nobuo; Podjarny, A. D.; International Union of Crystallography (Oxford : Oxford University Press, 2011)
This text is dedicated to the emerging field of neutron protein crystallography (NPC). It covers all of the practical aspects of NPC and demonstrates how NPC can explore protein features such as hydrogen bonds, protonation and deprotonation of amino acid residues, and hydration structures.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Crystallography; Neutrons -- Diffraction; Neutron sources; Proteins -- Structure